Synergism Among the Four Tobacco Bushy Top Disease Casual Agents in Symptom Induction and Aphid Transmission - Chen, Xiaojiao; Luo, Hengming; Zhang, Jingyi; Ma, Yan; Li, Kehua; Xiong, Feng; Yang, Yahui; Yang, Jiazhen; Lan, Pingxiu; Wei, Taiyun; Xu, Yi; Chen, Hairu; et al. (Frontiers in Microbiology, 2022)
Tobacco bushy top disease (TBTD), caused by multiple pathogens including tobacco bushy top virus (TBTV), tobacco vein distorting virus (TVDV), TBTV satellite RNA (TBTVsatRNA), and TVDV associated RNA (TVDVaRNA), is a destructive disease in tobacco fields. To date, how these causal agents are co-transmitted by aphid vectors in field and their roles in disease symptom induction remain largely unknown, due mainly to the lack of purified causal agents. In this study, we have constructed four full-length infectious clones, representing the Yunnan Kunming isolates of TVDV, TBTV, TBTVsatRNA, and TVDVaRNA (TVDV-YK, TBTV-YK, TBTVsatRNA-YK, and TVDVaRNA-YK), respectively. Co-inoculation of these four causal agents to tobacco K326 plants caused typical TBTD symptoms, including smaller leaves, necrosis, and plant stunting. In addition, inoculation of tobacco K326 plants with TBTV alone caused necrosis in systemic leaves by 7 dpi. Tobacco K326 and N. benthamiana plants infected by single virus or multiple viruses showed very different disease symptoms at various dpi. RT-PCR results indicated that co-infection of TVDVaRNA-YK could increase TVDV-YK or TBTV-YK accumulation in N. benthamiana plants, suggesting that TVDVaRNA-YK can facilitate TVDV-YK and TBTV-YK replication and/or movement in the infected plants. Aphid transmission assays showed that the successful transmission of TBTV-YK, TBTVsatRNA-YK, and TVDVaRNA-YK by Myzus persicae depended on the presence of TVDV-YK, while the presence of TBTVsatRNA-YK increased the aphid transmission efficiency of TBTV and TVDV. We consider that these four new infectious clones will allow us to further dissect the roles of these four causal agents in TBTD induction as well as aphid transmission.